Pengaruh Word of Mouth, Price, dan Product Quality terhadap Keputusan Pembelian (Studi pada Cafe Lelette Kopi Sigura-gura Sukun Malang) - Ahmad Amirudin; Agus Widarko; Muhammad Tody Arsyianto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to examine and determine the effect of Word of Mouth, Price, and Product Quality on Purchasing Decisions (Studies on of Café Lelette Kopi Sigura-gura Sukun Malang). This research is a type of quantitative research. The method used is multiple linear regression. The sampling technique uses the formula from Malhotra with a calculation of 90 samples. To solve the problems in this study using SPSS with the help of validity test, reliability test, normality test, multiple linear regression analysis, multicollinearity test, heteroscedasticity test, F test, and t test. The results showed that word of mouth (X1), price (X2), and product quality (X3) simultaneously had a significant effect on purchasing decisions (Y). Partial research results show that Word of Mouth (X1) and Price (X2) partially have a significant effect on Purchase Decision (Y). While Product Quality (X3) is partially insignificant to Purchase Decision (Y). Keywords: Word of Mouth, Price, Product Quality, Purchase Decision.